The barriers and strategy of Sota’s border tourism area development - Machya Astuti Dewi; Iva Rachmawati (Masyarakat, Kebudayaan dan Politik, 2018)
Merauke, located in the eastern part of Indonesia, has abundant natural resources and tourism potential. Unfortunately, these assets are not enough to establish Merauke as a successful border area. Even though many programs have been created by the local government of Merauke, the management of the border area in Sota Merauke has not been successful. This phenomenon poses a question about the barrier of developing Sota as a border tourism area. The research used qualitative methods by searching for related documents, observing Sota, and interviewing key persons including the local secretary of Merauke, the staff members of the local government of Merauke, the chief of police in Sota, WWF activists, and community leaders in Sota. The research found that the development of Sota as a border tourism area was not running well because of the lack of natural resource management, the lack of qualified human resources, and the lack of infrastructures with many institutional problems in those that did exist. The lack of qualified human resources was the most dominant factor because of the low ethos in the local community focused on developing the border area. The strategies proposed to tackle the barriers are: 1) to generate participation, especially that of youths and women, 2) to encourage tourism-aware groups, 3) to continuously implement group supervision, and 4) to develop border festivals with various cultural attractions and culinary promotions that involve a broad spectrum of Sota people.